Pengaruh Pergerakan Exchange Rate Terhadap Trade Balance dan Cash Flow di PT. XYZ - Rudy Riyanto P. Siahaan; Muhammad Bob Iqbal; Wisudanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The exchange rate refers to the price of one currency measured in another currency. Changes in the exchange rate can have a significant impact on the trade balance, investment flows, and cash flow of multinational companies. PT. XYZ, a manufacturing company in the automotive sector, is a subsidiary of a Global brand that has been operating since 1971, focusing on exporting cars and components produced in Indonesia to various countries worldwide. This study aims to analyze the relationship between exchange rate movements and cash flow movements at PT. XYZ using regression analysis involving hypothesis testing, linearity tests, and coefficient tests. The results indicate that there is a statistically significant relationship between the exchange rate and trade balance, suggesting that risk management for exchange rate movements is necessary to manage the impact on the trade balance, while the relationship between exchange rate and cash flow operating does not show a statistically significant relationship.